Elements of militarisation of the Atbasar and Botai cultures of Northern Kazakhstan - Baigunakov, Dosbol S.; Zaibert, Victor F.; Sabdenova, Gulmira E. (Journal of the Belarusian State University. History, 2022)
The huge changes that took place after the domestication of the horse at the beginning of the paleometall in the field of material and spiritual culture, in the social organisation of societies, undoubtedly affected the production of various tools. There were new types of tools that could be used as weapons. The tips of spears, arrows, darts, knives, harpoons, hammers, bolas and other artifacts from more than two hundred sites of Northern Kazakhstan, related to the Atbasar (7000–3000 BC) and Botai (4000–3000 BC) cultures give an opportunity to consider questions of forms of early militarisation of ancient societies. Some tools, their seriality and significant standardisation indicate that they could be universal and complex, they were used in agriculture, as well as in military clashes. After the domestication of the horse, the world of paleometall entered a new generation of wars aimed at the direct destruction of the enemy by cavalry. This is a fundamental change in the nature of armed conflicts, the transformation of the content of war or armed struggle in Antiquity. If the hostile conflicts among hunter-gatherers, which were the bearers of the Atbasar culture, are primarily local, then for the Botai people they are already reaching the interregional level.